2007
DOI: 10.1159/000103304
|View full text |Cite
|
Sign up to set email alerts
|

S100B Is Not a Reliable Prognostic Index in Paediatric TBI

Abstract: Background: As far as paediatric traumatic brain injury is concerned, it is difficult to quantify the extent of the primary insult, to monitor secondary changes and to predict neurological outcomes by means of the currently used diagnostic tools: physical examination, Glasgow Coma Scale (GCS) score and computed tomography. For this reason, several papers focused on the use of biochemical markers (S100B, neuron-specific enolase) to detect and define the severity of brain damage and predict outcome after traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 66 publications
(31 reference statements)
0
41
0
3
Order By: Relevance
“…130 As with all biomarkers, the role of S100B in TBI management in children is even less clear, 131 with some arguing that this marker has little diagnostic or prognostic utility in paediatric populations. 132 In a study of children with TBI aged ≤15 years, those <5 years or >9 years of age had higher serum levels of S100B than did those aged 5-9 years. 133 S100B may, therefore, be an inadequate marker to distinguish between symptomatic and asymptomatic children with concussion, 133 and the utility of S100B in diagnostics and outcome prognosis is questionable.…”
Section: Fluid-based Biomarkersmentioning
confidence: 96%
“…130 As with all biomarkers, the role of S100B in TBI management in children is even less clear, 131 with some arguing that this marker has little diagnostic or prognostic utility in paediatric populations. 132 In a study of children with TBI aged ≤15 years, those <5 years or >9 years of age had higher serum levels of S100B than did those aged 5-9 years. 133 S100B may, therefore, be an inadequate marker to distinguish between symptomatic and asymptomatic children with concussion, 133 and the utility of S100B in diagnostics and outcome prognosis is questionable.…”
Section: Fluid-based Biomarkersmentioning
confidence: 96%
“…However, some studies reported a poor value of S100B as a predictor of outcome after brain injury, particularly mild and pediatric TBI. A poor correlation was found between serum and brain S100B values, suggesting that the serum levels may depend primarily on the integrity of the blood-brain-barrier and do not reflect the S100B levels in the brain 6,15 . Despite apparent controversy, S100B still has potential as a brain injury biomarker, and its preclinical and clinical utility should be further explored.…”
mentioning
confidence: 89%
“…This has raised concerns as to whether the serum levels of this protein actually correlate with the degree of brain damage or are more reflective of other processes. Finally, because of the high normative values in the pediatric population, S100B is not a useful marker in children (Piazza et al 2007, Berger et al 2006.…”
Section: S100bmentioning
confidence: 99%